Sustaining reductions in postoperative nausea and vomiting after evidence-based practice initiative: A success story - Christopher A Smith; Richard E Haas (Journal of Health and Social Sciences)
Background: Postoperative nausea and vomiting (PONV) remains a signifi cant problem in the surgical population. Many researchers have demonstrated signifi cant reductions in institutional PONV when risk screening and antiemetic prophylaxis protocols are implemented. These protocols have not been universally adopted. Our adoption and implementation led to signifi cant reductions in PONV. The challenge is to sustain these reductions over time. Methods: A retrospective cohort chart review of consecutive surgical patients (n = 1002) during the period encompassing October through November of 2016, the sustainability group (G16). Descriptive statistics were used to compare G16 with the implementation group (G14) in regard to demographic data, and Z-score and Chi-square (χ2) statistics were utilized to determine levels of signifi cance. Correlations were calculated to determine levels of compliance to the protocol and the incidence of PONV. Results: A significant (P = 0.0007) reduction in PONV incidence was identified as 8.5% (85/1002) in G16 compared to 13.4% (134/997) achieved in G14. Overall compliance with the targeted prophylaxis protocol was 87.2% (G16, 874/1002), a significant (P = 0.0001) improvement compared to 79% (G14, 788/997). A 61.1% (11/18) incidence of PONV in laparoscopic gastric bypass patients was identifi ed in the G16 group. Conclusions: Initial reductions in PONV were not only sustained but significantly improved. Preoperative risk assessment for PONV, risk stratification, and fidelity to anti-emetic prophylaxis protocols reduce the incidence of PONV in the post-anesthesia care unit. High-risk patients require three or more interventions to obtain acceptable reductions in PONV. Laparoscopic gastric bypass patients remain a high-risk group requiring aggressive multimodal prophylaxis beyond their Apfel simplifi ed risk score.